Effect of Nutrients on Environmental Sex Determination and Size of Gametophytes in Culcita macrocarpa (Journal of Life and Earth Science, 2014)
In environmental sex determination (ESD) gender is decided after conception, depending on the environment, rather than being genetically fixed. ESD has rarely been studied in homosporous ferns. In the present study, Culcita macrocarpa gametophytes were cultured under varying nutrient conditions. Initially, most of the gametophytes of Culcita macrocarpa were male and subsequently hermaphrodite under different nutrition. The result indicates that its sex determination is protandry. All nutrient conditions were favourable for developing male prothalli but only good environment (high nutrient) was favourable for female gametophyte growth. In all respects, female gametophytes were much larger, than the other types of gametophytes. Hermaphroditic gametophytes were larger than male gametophytes, which were larger than asexual gametophytes. DOI: http://dx.doi.org/10.3329/jles.v7i0.20130 J. Life Earth Sci., Vol. 7: 109-113, 2012